Dynamics analysis of novel hybrid robotic arm with three fingers. Issue 12 (28th May 2015) - Lu, Yi; Dai, Zhuohong; Ye, Nijia
SUMMARY: A novel hybrid robotic arm with three fingers is proposed for assembly, operation and rescue. It is composed of an upper 3RPS-type parallel manipulator, a lower 3SPR-type parallel manipulator and three fingers. Its dynamics are studied and analyzed systematically. First, the kinematics formulae of the moving links at their mass centers in the hybrid robotic arm with three fingers are established. Second, the formulae for solving the inertial wrench of the moving links at their mass centers are derived. Third, a dynamics formula is established for solving the dynamic active/constrained forces of the hybrid robotic arm and the fingers. Finally, an analytic example is given for solving the kinematics and dynamics of the hybrid robotic arm with three fingers and the analytic solved solutions are verified by a simulation mechanism.